2016
DOI: 10.3389/fmats.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Crystal Growth in Laser-Patterned Lines in Glasses

Abstract: Laser-induced crystallization is a new method for the design and control of the crystallization of glasses and opens a new door in the study of nucleation and crystal growth in glasses. Nonlinear optical Sm-doped β-BaB2O4 (β-BBO) crystal lines were patterned by continuous-wave Yb:YVO4 fiber laser (wavelength 1080 nm) in 8Sm2O3-42BaO-50B2O3 glass as an example, and nucleation and crystal growth behaviors in the laser-patterned bending and crossing lines were examined. It was confirmed that the growth of c-axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
(37 reference statements)
2
34
0
Order By: Relevance
“…It is, therefore, suggested that the feature of the growth of LiNbO 3 in 3NiO‐LNS glass in an electric furnace appears depending on laser irradiation condition even in the laser‐induced crystallization. It should be pointed out that in the patterning of β‐BaB 2 O 4 crystal (β‐BBO) lines by laser irradiations, only the c ‐axis oriented β‐BBO (a uniaxial and negative crystal similar to LiNbO 3 ) crystals are achieved, because β‐BBO has a layered crystal structure and hence the degree of the anisotropy of atom packing between a ‐axis and c ‐axis is very large.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, suggested that the feature of the growth of LiNbO 3 in 3NiO‐LNS glass in an electric furnace appears depending on laser irradiation condition even in the laser‐induced crystallization. It should be pointed out that in the patterning of β‐BaB 2 O 4 crystal (β‐BBO) lines by laser irradiations, only the c ‐axis oriented β‐BBO (a uniaxial and negative crystal similar to LiNbO 3 ) crystals are achieved, because β‐BBO has a layered crystal structure and hence the degree of the anisotropy of atom packing between a ‐axis and c ‐axis is very large.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization of glasses is regarded as the formation process of self‐organized structures and is one of the most important fundamental technologies for the creation of materials, in which nucleation and crystal growth are controlled and crystals with desired morphologies and orientations are designed . Laser irradiation of glasses receives considerable attention as a new tool of the spatially selected patterning of crystals in glasses, that is, laser‐induced crystallization, which is really a new challenge in the science and technology of materials including glasses and also opens a new door to the crystal growth engineering …”
Section: Introductionmentioning
confidence: 99%
“…With those properties, we showed it is possible to control the orientation of LiNbO3 nanocrystals appearing at low fs pulse energy, with the laser polarization [17]. This was a breakthrough in material science, whereas at high pulse energy, the crystallization grains are larger with the polar axis directed along the laser scanning direction whatever the laser polarization orientation as it is the case in many publications [7,8].…”
Section: Introductionmentioning
confidence: 74%
“…Crystallization of glass is one of the easy and low-cost techniques to explore and fabricate new nonlinear optical materials for integrated optic devices. Up to now, several methods, including thermal gradient [4], ultrasonic surface treatment [5] and continuous wave laser irradiation [6] [7], have been proposed to facilitate a controlled crystallization. However, these methods do not allow the control of the crystals' space distribution in volume, whereas it is a key point for the applications in integrated optics.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the crystallization is induced in these laser irradiation conditions. The line patterned with S = 2.3 m/s shows a relatively homogeneous distribution in color along the laser scanning direction, indicating that a stable structural change is taking place under this laser irradiation condition and thus the patterning of highly oriented crystal line [5,28,29]. On the other hand, in other conditions, the color of the lines is not homogeneous, indicating the random orientation of crystals.…”
Section: Laser Pattering Of Crystal Linesmentioning
confidence: 92%